Kecepatan Putaran Poros Pada Mesin Pembuat Pakan Pelet Berpenggerak Kayuh Sepeda - Nugroho, Adi; Wibowonoto, Arif (TEKNIK, 2017)
The background of this study is the human power inconsistensy to run the simple pellets machine spinner. One of the efforts is to use bicycle sprocket to transmit the power until it reaches the expected speed. The exact size of spocket is needed to gain the wanted speed which will be obtained through the speed rotation test on various size of spocket. Data collecting methode that are used on this study are literature study and observation. While data analysis is using parametric analysis technique and the measurement parameter variables are spocket size and axis spin speed (rpm). This research aims to determine the exact size of sprocket in order to reach 626 rpm. As it result is required 54 rpm at Nâ‚‚ (18 T), 63 rpm at Nâ‚‚ (21 T), and 72 rpm at Nâ‚‚ (24 T) to reach 626 rpm. And the size of spockets are Nâ‚ (34 T), Nâ‚‚ (18 T, 21 T, 24 T), Nâ‚ƒ (42 T), Nâ‚„ (11T), Nâ‚… (24 T) and Nâ‚† (15 T).